Bone grafting of the regenerate: a previously undescribed case and surgical technique - Abdalla, Mazen`; Giannikas, Konstantinos (International Journal of Research in Orthopaedics, 2020)
Distraction osteogenesis can occasionally be complicated with poor-quality regenerated bone. Several factors have been identified in the literature in order to reinforce the maturation of the regenerate. We would like to present a case in a 40 years old patient who presented with shortening and uniplanar varus angulation at his proximal tibia. The patient was treated with distraction osteogenesis using a circular frame. He had significant delay in the maturation of the 4-5 cm gap, and it was decided to use a non-vascularized fibular graft that was introduced using the tibial intramedullary nailing instrumentation. The graft led to an impressive acceleration of the maturation of the regenerate, mostly posteriorly and laterally with poor progression at the anterior part of the tibia. As this is the first such case presented in the international literature it is difficult to speculate why the regenerate was stimulated only in specific areas. Further reporting is necessary to reach safe conclusions.